Anti-bullying procedures for schools in Ireland: principals' responses and perceptions. (3rd April 2018) - Foody, Mairéad; Murphy, Helena; Downes, Paul; O'Higgins Norman, James
Abstract: The role of the principal is imperative in creating a school climate that nurtures differences and equality at the same time. Policy and legislation in Ireland dictates the responsibility of school principals in preventing and intervening in issues relating to bullying. The current research investigates the extent to which principals consider the impact of bullying on their students and the strategies they take to combat it in their schools. We consider how principals respond to bullying and what supports they feel are missing for them to adhere to relevant policy. A sample of 918 principals from a range of schools across Ireland completed an online survey. The results demonstrated some positive actions by principals such as the provision of anti-bullying policies. However, they also document areas that need more action such as increased access to counsellors and appointing a specific staff member to deal with and tackle bullying in each school. Guidance from the Department of Education and Skills in Ireland on the development and provision of an anti-bullying programme is called for. Results are discussed in light of the current Anti-Bullying Procedures established by the Department of Education and Skills and the Action Plan for Bullying 2013.